2022
DOI: 10.3389/fvets.2022.964027
|View full text |Cite
|
Sign up to set email alerts
|

Lactate uptake in the rumen and its contributions to subacute rumen acidosis of goats induced by high-grain diets

Abstract: Rumen acidosis is the consequence of feeding rapidly fermentable grain diets and it is considered the most common nutritional disorder in intensive feeding ruminants. Due to that mechanism of catabolism and transformation is driven by multi-factors, the role of ruminal lactate and its contribution to subacute rumen acidosis has not been well defined yet. The aim of this study is to evaluate the effects of SARA on the production, absorption, circulation, and transformation of lactate in the rumen. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
1
6
0
2
Order By: Relevance
“…However, McCann et al [ 46 ] observed no significant change in M. elsdenii RA upon SARA induction. He et al [ 47 ] reported a twofold increase in the relative abundance of M. elsdenii in non-lactating Saanen goats undergoing induction of SARA (elicited through high-concentrate feeding) compared with herdmates not subjected to SARA induction.…”
Section: Abundance In the Rumenmentioning
confidence: 99%
See 1 more Smart Citation
“…However, McCann et al [ 46 ] observed no significant change in M. elsdenii RA upon SARA induction. He et al [ 47 ] reported a twofold increase in the relative abundance of M. elsdenii in non-lactating Saanen goats undergoing induction of SARA (elicited through high-concentrate feeding) compared with herdmates not subjected to SARA induction.…”
Section: Abundance In the Rumenmentioning
confidence: 99%
“…From a producer standpoint, the development of stable commercial products for frequent oral dosing to animals is essential for establishing the strain in the rumen in commercial herds under production conditions, or at least for maintaining a sufficient abundance between administrations of dosing, in order to achieve the goal of controlling acidosis. Finally, it is worth mentioning that any success of the probiotic M. elsdenii in controlling acute lactic acidosis may be compromised somewhat by the conversion of lactic acid to other VFAs (particularly butyric) with a resulting increased propensity to trigger SARA [ 47 ].…”
Section: Nutritional Importancementioning
confidence: 99%
“…La acidosis ruminal es un trastorno digestivo como consecuencia de la alimentación con dietas de granos rápidamente fermentables, considerada como el trastorno nutricional más común en tanto en el ganado de carne como en el de leche de alimentación intensiva (He et al, 2022). Hay dos variantes de acidosis ruminal, la acidosis ruminal aguda (ARA) y la acidosis ruminal subaguda (SARA).…”
Section: Acidosis Lácticaunclassified
“…En ambos casos el metabolito responsable es el ácido láctico o lactato, un producto intermediario en la fermentación microbial de los carbohidratos para su conversión en ácidos grasos volátiles, especialmente ácido propiónico. El lactato en el rumen es producido principalmente por la fermentación del almidón por Streptococcus bovis y catabolizado por lactato deshidrogenasa (LDH) de bacterias que utilizan lactato como Megasphaera elsdenii y Selenomonas ruminantium en el rumen (He et al, 2022).…”
Section: Acidosis Lácticaunclassified
“…Short-chain fatty acids (SCFA), also called volatile fatty acids (VFA) are the products of feed fermentation in the rumen [ 1 ], whereas D-/L-lactate are the intermediate products of starch fermentation in the rumen [ 2 ]. Given ruminal SCFA and lactate profiles are associated with ruminant feeding regime, ruminal microbial composition, as well as ruminal acidosis severity [ 1 ].…”
Section: Introductionmentioning
confidence: 99%